Efficient separation of silica and alumina in simulated CFB slag by reduction roasting-alkaline leaching process. (15th March 2019) - Li, Xiaobin; Wang, Hongyang; Zhou, Qiusheng; Qi, Tiangui; Liu, Guihua; Peng, Zhihong
Highlights: Efficient separation of alumina and silica in roasted coal gangue can be realized. The transformation of roasted coal gangue into hercynite and free silica is achieved. More than 95% silica in the reduction roasted product is extracted by alkaline leaching. The leached residue is a decent raw material for alumina extraction by the Bayer digestion. Abstract: Although circulating fluidized bed (CFB) combustion technology is regarded as an efficient technology to use abundant coal gangue as fuel, large amounts of CFB slag has to be stockpiled and raises the environmental stress. This work focused on the comprehensive utilization of silica and alumina in CFB slag. The combustion process of coal gangue and the subsequent separation of alumina and silica by alkaline leaching of the simulated CFB slag were investigated. The results show that, in the combustion process, kaolinite in coal gangue firstly converts into meta-kaolinite at 600–900 °C due to dehydroxylation, and then the meta-kaolinite splits into mullite and amorphous silica at ≥1000 °C. Whereas by reduction roasting with hematite, the CFB slag simulated at 800–1100 °C can be completely converted into hercynite and free silica in forms of quartz solid solution and cristobalite solid solution. However, the conversion reaction rate for the CFB slag simulated at 1200 °C decreases significantly due to the formation of well crystallized mullite prior to the reduction roasting. Additionally, either quartz solid solution or cristobalite solid solution is readily soluble and hercynite is insoluble in alkaline solution. Under optimal conditions, more than 95% of silica in the reduction roasted product can be dissolved in alkaline solution and the mass ratio of alumina to silica in the leached residue can increase from 0.85 to above 20. This study lays a foundation for developing a novel technique to efficiently recycle the carbon, silica and alumina in coal gangue and thus to alleviate the environmental stress.